Utilizing Innovative Instructional Strategies Towards More Learner-Friendly Teaching and Learning - Onuebunwa, S.E. (Richtmann Publishing, 2012)
The paper focuses on instructional strategies that not only involves the learner but generally makes the teaching andlearning environment challenging, stimulating and meaningful. A number of such innovative techniques that are learner friendlywere discussed pointing out some possible ways of utilizing them for specific instructional purposes. The key issue of learnercenterednessand it’s hallmarks were highlighted in the discussion while major constraints such as limited facilities, large classesand structured syllabus were noted. However the paper emphasized the role of interest and commitment towards reducing theeffects of these constraints.